2020
DOI: 10.3390/galaxies8010016
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Planets in Binaries

Abstract: The frequency of planets in binaries is an important issue in the field of extrasolar planet studies because of its relevance in the estimation of the global planet population of our galaxy and the clues it can give to our understanding of planet formation and evolution. Multiple stars have often been excluded from exoplanet searches, especially those performed using the radial velocity technique, due to the technical challenges posed by such targets. As a consequence and despite recent efforts, our knowledge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…A shortfall of close binaries (<50-100 AU) among planet hosts has been vastly reported in observational surveys (Roell et al, 2012;Bergfors et al, 2013;Wang et al, 2014;Kraus et al, 2016;Moe and Kratter, 2019;Bonavita and Desidera, 2020). This feature is generally attributed to a hindrance of planet formation in very tight binaries, and is also predicted in theoretical models (Thebault and Haghighipour, 2015).…”
Section: Completeness and Survey Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…A shortfall of close binaries (<50-100 AU) among planet hosts has been vastly reported in observational surveys (Roell et al, 2012;Bergfors et al, 2013;Wang et al, 2014;Kraus et al, 2016;Moe and Kratter, 2019;Bonavita and Desidera, 2020). This feature is generally attributed to a hindrance of planet formation in very tight binaries, and is also predicted in theoretical models (Thebault and Haghighipour, 2015).…”
Section: Completeness and Survey Limitationsmentioning
confidence: 77%
“…We complemented the multiplicity data from these databases with the Catalogue of Exoplanets in Binary Star Systems 5 (Schwarz et al, 2016). We added to this all systems from published surveys searching for visual stellar companions to circumprimary planetary systems (Luhman and Jayawardhana, 2002;Patience et al, 2002;Udry et al, 2004;Mugrauer et al, 2006;Mugrauer et al, 2007a;Mugrauer et al, 2007b;Raghavan et al, 2006;, Eggenberger et al, 2011Daemgen et al, 2009;Mugrauer and Neuhäuser, 2009;Adams et al, 2012;Adams et al, 2013;Ginski et al, 2012, Ginski et al, 2016Ginski et al, 2020;Lillo-Box et al, 2012;Bergfors et al, 2013;Faedi et al, 2013;Lodieu et al, 2014;Wang et al, 2014;Mugrauer and Ginski, 2015;Wöllert et al, 2015;Deacon et al, 2016;Kraus et al, 2016;Ngo et al, 2016;Ngo et al, 2017;Furlan et al, 2017;Moutou et al, 2017;Coker et al, 2018;Dietrich and Ginski, 2018;Ziegler et al, 2018;Fontanive et al, 2019;Mugrauer, 2019;Bohn et al, 2020;Southworth et al, 2020) or reviews of planets in binaries (Bonavita and Desidera, 2007;Bonavita and Desidera, 2020;…”
Section: Binaries In Surveys and The Literaturementioning
confidence: 99%
“…Despite the potential complications for planet formation induced by the gravitational perturbations from the binary, more than 100 planets in binary systems have already been discovered (e.g., Martin 2018;Bonavita & Desidera 2020) 1 . Most of these planets are found to orbit only one of the binary stars (i.e., 'S-type ', i.e., circumstellar planets).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the drop, the order of the top five candidates for the study remains the same, although changes would be necessary to prioritize repeated observations (see Table 4). However, a more recent study found that although there is reduction in occurrence rate for binaries with a critical radius < 2.5 AU, there is a boosted rate when the critical radius > 3 AU (Bonavita & Desidera 2020, cf. Fontanive & Bardalez Gagliuffi 2021.…”
Section: Discussionmentioning
confidence: 96%